2012
DOI: 10.1007/s11274-012-1143-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucose concentration on the rate of fructose consumption in native strains isolated from the fermentation of Agave duranguensis

Abstract: Studies on hexose consumption by Saccharomyces cerevisiae show that glucose is consumed faster than fructose when both are present (9:1 fructose to glucose) in the medium during the fermentation of Agave. The objective of this work was to select strains of S. cerevisiae that consume fructose equal to or faster than glucose at high fructose concentrations by analyzing the influence of different glucose concentrations on the fructose consumption rate. The optimal growth conditions were determined by a kinetics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The yeasts employed in this paper were commercial baker's yeast, Saccharomyces cerevisiae ITD00196 (Díaz-Campillo et al, 2012), Scheffersomyces stipitis ATCC58785, Scheffersomyces stipitis Y-17104, Kluyveromyces marxianus CBS6556, and Schwanniomyces occidentalis ATCC26077. The inoculum production assays were carried out with conventional, coiled, and baffled 250 mL Erlenmeyer flasks (Pyrex, Borosilicate glass, USA), as reported by Marín-Palacio et al (2014).…”
Section: Yeast and Inoculum Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The yeasts employed in this paper were commercial baker's yeast, Saccharomyces cerevisiae ITD00196 (Díaz-Campillo et al, 2012), Scheffersomyces stipitis ATCC58785, Scheffersomyces stipitis Y-17104, Kluyveromyces marxianus CBS6556, and Schwanniomyces occidentalis ATCC26077. The inoculum production assays were carried out with conventional, coiled, and baffled 250 mL Erlenmeyer flasks (Pyrex, Borosilicate glass, USA), as reported by Marín-Palacio et al (2014).…”
Section: Yeast and Inoculum Productionmentioning
confidence: 99%
“…The agitation in the bioreactor could help the homogenization of the SSM and improve the speed of the process. The yeast S. cerevisiae ITD00196 was selected because it has been characterized for ethanol production (Díaz-Campillo et al, 2012). The possibility of producing ethanol with a pilot batch bioreactor using 25 kg WM of the SSM without any thermochemical or enzymatic pre-treatment was demonstrated, however, differences were found that could be diminished with better control of the process, using, for example, a thermal pretreatment (Estrada-Martínez et al, 2019).…”
Section: Ethanol Production In the Ssc Of The Ssmmentioning
confidence: 99%